1995
DOI: 10.1117/12.207438
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and microstructural effects of nanosecond pulsed Nd:YAG laser irradiation on tooth root surface

Abstract: Plaque, calculus and altered cementum removal by scaling and root planing is a fundamental procedure in periodontal treatment. However, the residual smear layer contains cytotoxic and inflammatory mediators which adversely affect healing. Chemical smear layer removal is also problematic.In previous investigations effective smear layer removal was achieved using long pulsed irradiation at 1.06u. However, laser irradiation was not adequate as an alternative to scaling and root planing procedures and concurrent t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…With increased interest in the use of infrared imaging devices to assess the temperature of mineralized tooth tissue, it is relevant to assess the emissivity of each sample to report a valid temperature. Many in vitro studies have been carried out with thermal imaging devices to assess potential damage to both the soft and mineralized tooth tissue from temperature changes, e.g., during laser application ( Launay, et al, 1987 ; Pogrel, et al, 1988 ; Anić, et al, 1993 ; Arima & Matsumoto, 1993 ; Neev, et al, 1993 ; Arrastia, et al, 1994 ; Anić and Matsumoto, 1995 ; Arrastia, et al, 1995 ; Machida, et al, 1995 ; Wilder-Smith, et al, 1995 ; Anić, et al, 1996a ; Anić, et al, 1996b ; Meyer & Foth, 1996 ; Neev, et al, 1996 ; Whitters & Strang, 2000 ; Yu, et al, 2000 ; Yamazaki, et al, 2001 ; Kishen, et al, 2003 ; Ishizaki, et al, 2004 ; Madura, et al, 2004 ; Wang, et al, 2005 ; Ana, et al, 2007 ; Da Costa Ribeiro, et al, 2007 ; Stock, et al, 2011 ; Da Silva Barbosa, et al, 2013 ; Uzunov, et al, 2014 ; Forjaz, et al, 2022 ), light-curing-composite ( Al-Qudah, et al, 2005 ; Bouillaguet, et al, 2005 ; Aksakalli, et al, 2014 ; Jo, et al, 2019 ; Mouhat, et al, 2021 ), endodontic treatment ( McCullagh, et al, 1997 ; McCullagh, et al, 2000 ; Behnia & McDonald, 2001 ; Lipski and Zapałowicz, 2002 ; Lipski & Woźniak, 2003 ; Lipski, 2004 ; Lipski, 2005a ; Lipski, 2005b ; Lipski, 2006 ; Hsieh, et al, 2007 ; Ulusoy, et al, 2015 ; Diegritz et al, 2020 ; Podolak, et al, 2020 ), pin-placement ( Biagioni, et al, 1996 ), post-removal ( Budd, et al, 2005 ; Lipski et al, 2010a ), cavity preparation and r...…”
Section: Introductionmentioning
confidence: 99%
“…With increased interest in the use of infrared imaging devices to assess the temperature of mineralized tooth tissue, it is relevant to assess the emissivity of each sample to report a valid temperature. Many in vitro studies have been carried out with thermal imaging devices to assess potential damage to both the soft and mineralized tooth tissue from temperature changes, e.g., during laser application ( Launay, et al, 1987 ; Pogrel, et al, 1988 ; Anić, et al, 1993 ; Arima & Matsumoto, 1993 ; Neev, et al, 1993 ; Arrastia, et al, 1994 ; Anić and Matsumoto, 1995 ; Arrastia, et al, 1995 ; Machida, et al, 1995 ; Wilder-Smith, et al, 1995 ; Anić, et al, 1996a ; Anić, et al, 1996b ; Meyer & Foth, 1996 ; Neev, et al, 1996 ; Whitters & Strang, 2000 ; Yu, et al, 2000 ; Yamazaki, et al, 2001 ; Kishen, et al, 2003 ; Ishizaki, et al, 2004 ; Madura, et al, 2004 ; Wang, et al, 2005 ; Ana, et al, 2007 ; Da Costa Ribeiro, et al, 2007 ; Stock, et al, 2011 ; Da Silva Barbosa, et al, 2013 ; Uzunov, et al, 2014 ; Forjaz, et al, 2022 ), light-curing-composite ( Al-Qudah, et al, 2005 ; Bouillaguet, et al, 2005 ; Aksakalli, et al, 2014 ; Jo, et al, 2019 ; Mouhat, et al, 2021 ), endodontic treatment ( McCullagh, et al, 1997 ; McCullagh, et al, 2000 ; Behnia & McDonald, 2001 ; Lipski and Zapałowicz, 2002 ; Lipski & Woźniak, 2003 ; Lipski, 2004 ; Lipski, 2005a ; Lipski, 2005b ; Lipski, 2006 ; Hsieh, et al, 2007 ; Ulusoy, et al, 2015 ; Diegritz et al, 2020 ; Podolak, et al, 2020 ), pin-placement ( Biagioni, et al, 1996 ), post-removal ( Budd, et al, 2005 ; Lipski et al, 2010a ), cavity preparation and r...…”
Section: Introductionmentioning
confidence: 99%
“…Thus, short laser pulses can result in reduced collateral, thermal and structural damage. Thermal studies performed using the nanosecond-pulsed Nd-YAG laser have indeed demonstrated the capability of this laser to ablate dentin with reduced thermal effects in adjacent dental tissues (22,(24)(25)(26), as compared with those of conventional Nd-YAG lasers available to dental clinicians.…”
Section: Introductionmentioning
confidence: 99%